EM-TECHNOLOGIES APPLICATION IN CITY WATER PURIFICATION SYSTEMS - Vovk, Oksana O.; Guy, Angela E.; Seliverstov, Mykola O. (Proceedings of National Aviation University (archive), 2010)
In this article it is considered a problem of inefficient sewage treatment in a result of the outdated equipment application. Under restrictions of heavy economic crisis, when expensive and material-intensive systems of clearing cease to be actual it was proposed application of EM-technologies in order to improve water purification city systems